Fabrikasi Lapisan Nano Fluorine Doped Tin Oxide (FTO) Dengan Variasi Temperature Menghasilkan Material Bersifat Transparan dan Konduktif - Yusuf, Mirza; Suciatno, Suciatno (Universitas Muhammadiyah Yogyakarta, 2020)
The process of forming a doped Tin oxide (FTO) nano fluoride layer was made using Tin Chloride (SNCL2) with Ammonium Fluoride (NH4F) mixing process using a magnetic stirrer at room temperature (28oC). The solvent liquid uses 99% ethanol. Both of these solutions are mixing and finally get the fluorinated doped fluorine Tin. The deposition method of the nanolayer uses the pyrolysis process to produce FTO substrates. This research focused on the production of materials that have transparent properties and have conductivity values. It based on the requirements of work solar cells to work. The process of measuring transparency uses an absorbance measurement tool. Measurement of conductivity using a conductivity meter with a 4-point circular Probe method used in this study was divided into four variations, including starting from 400, 425, 450, 475, 500 degrees Celsius. From this method, the best results were obtained at a temperature of 475 degrees Celsius with an average value of 25 Î© / cm and the highest percentage of transmittance.